Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Colmenares García, Nicole (2018)
The present investigation case is focused on the development of a strategic plan for the Fast Retailing company to enter the peruvian market. Fast Retailing is one of the biggest groups in the fashion and fast fashion industries worldwide. It competes with Inditex and H&M, where it ranks third. Its objective is to become the number one retailer in the world and to achieve this, its brand UNIQLO is the main focus.